Superheated steam temperature control for boiler using adaptive dynamic feedforward compensators - Ha, Nguyen Trong; Hoa, Nguyen Le; Vinh, Doan Quang (Vietnam Journal of Science and Technology, 2018)
This paper proposes a new control strategy for improving the performance of the superheated steam temperature control system in thermal power plants. Based on the analysis of the limitations of the static feedforward compensators (SFC) for temperature and boiler load disturbances in the existing control system of the auxiliary boiler in Dung Quat refinery, two adaptive dynamic feedforward compensators (ADFC) for temperature and boiler load disturbances were proposed to replace the SFCs. In addition, a method for predicting the tube wall temperature of the superheater using an autoregressive moving average (ARMA) model was also proposed. The simulation results for the two typical cases of the boiler load change indicate that the control system incorporated with the proposed ADFCs improves significantly the performance of the control system